The Application of Simple and Easy to Implement Decoupling Pulse Scheme Combinations to Effect Decoupling of Large J Values with Reduced Artifacts. (29th April 2014) - Klika, Karel D.
Abstract : Of the various problems in decoupling one nucleus type from another using standard decoupling pulse schemes for broadband decoupling, a particular challenge is to effect full, artifact-free decoupling when the size of the coupling constant is very large. Herein it is demonstrated that 1 H decoupling of the 31 P NMR spectrum of diethyl phosphonate HP(=O)(OCH2 CH3 )2 can be accomplished with reduced artifacts despite the large J H, P 1 value of 693 Hz by using a combination of decoupling pulse schemes involving continuous-wave (CW) irradiation and either adiabatic-pulse decoupling (APD), MPF decoupling, or traditional composite-pulse decoupling (CPD) schemes such as WALTZ or GARP. The considered strategy is simple, efficient, and easy to implement on most instruments. The best result was attained for a combination of CW and CPD using GARP with a standard pulse width of 60 μ s. Altogether, the advantages of the methodology include low power requirements, complete decoupling, tolerance of a range of large J values, large bandwidth for normal-sized J values, and the suppression of sidebands.